TINGKAT PEMAHAMAN MAHASISWA TERHADAP PEDOMAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) - Melkianus Suluh; Yuliana Sesi Bitu (Postgraduate, University of Mataram, 2018)
This study aims to: (1) determine the level of understanding of STKIP Weetebula students on RPP components, and (2) the ability of STKIP Weetebula students in preparing lesson plans. This research was conducted in Sumba Barat Daya District, East Nusa Tenggara. This research is a qualitative descriptive study. The research subjects were taken by purposive random sampling technique, as many as 40 people from 130 students spread over 4 study programs. Data collection uses an open questionnaire instrument and RPP format equipped with SK and KD according to the sub-field of research. The conclusion of the results of this study is first, students' understanding of the Learning Implementation Plan or RPP component is basically good, but in practice, students need to be trained to implement RPP. In addition, students 'understanding of the learning model needs to be improved, this is in line with the results of the students' work in preparing the student lesson plans, not paying enough attention to the model steps. Second, the ability to prepare lesson plans. Students in preparing lesson plans are generally good. The weakness of the student lies in the ability to describe KD in the form of indicators not yet answering the minimum KD standards, learning objectives have not shown goals that can be measured and achieved, to differentiate indicators from objectives, students only add student subjects, and use the same operational verbs for all purposes learning no mention of the forms of apperception activities carried out. At the core activities, the learning steps are not in accordance with the stages of the learning model, and in the final activity there is no explanation of the direct or indirect benefits of the material being taugh.Keywords: Student understanding, Learning Implementation Plan